(untitled) (Okhaldhunga Journal, 2025)
Human-Wildlife Conflict (HWC) creates major obstacles for biodiversity protection together with human safety worldwide because of habitat destruction and resource conflicts and changing climates. The research investigates HWC patterns and their impacts through various management strategies at both global and national levels with special emphasis on Nepal. HWC causes major financial losses and harms deaths and injuries to people worldwide through events like wildlife crop destruction and livestock predation and human attacks against wildlife. Nepal’s fiscal records from fiscal years 2075/76 to 2078/79 indicate developing human death rates and compensation payments that highlight the worsening wildlife-human conflicts. The implementation of effective HWC management requires organizations to establish both preventive strategies like electric fences and crop diversity along with mitigating strategies through compensation plans and community programs. The National Parks and Wildlife Conservation Act and Wildlife Damage Relief Guidelines of Nepal focus on establishing buffer zones and revenue-sharing and victim compensation within their policy framework. For long-term success it is necessary to unite local expertise with multi-sectoral cooperation and adaptable strategic plans. Although human-wildlife conflict remains a permanent threat scientists and community members can reduce its effects through combined prevention methods.